Strategi Peningkatan Pemahaman Agama Islam Anak melalui Implementasi Pesantren Kilat: Studi Nagari Lubuak Karak - Amilia Fajar Ayu; Asih Puspitasari; Gio Alfayed; M. Aji Latif; Faisal Hamzah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Islamic religious education plays a crucial role in shaping children's religious character in the digital age. One effective way to support this is through Islamic boarding schools (pesantren, Islamic boarding schools, short-term Islamic boarding school programs) as a form of intensive non-formal education. This study aims to analyze the contribution of Islamic boarding school activities to improving Islamic religious understanding among children in Lubuak Karak Village, IX Koto District. This study used a qualitative approach with a descriptive-evaluative design. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that Islamic boarding schools significantly improve children's religious understanding, both in terms of knowledge and worship practices, while simultaneously fostering religious character traits such as discipline and responsibility. Therefore, Islamic boarding schools can be considered an effective strategy for developing a generation with strong faith, good morals, and religious awareness.